PEMANFAATAN KARDUS BEKAS SEBAGAI ALAT PERMAINAN EDUKATIF UNTUK MENINGKATKAN KREATIVITAS ANAK DIDIK KELOMPOK BERMAIN - Wijayanti, Nurti (JIV-Jurnal Ilmiah Visi, 2006)
Creativity is one of the objectives for nonformal education. However, creativity is not well developed enough as it was observed at Play Group of Aisyiyah 02 Pati. Through waste cartoon, children can be trained to develop their creativity. The article reports the progress of how waste cartoons be made as puppets. It is an art work, and students should be creative. The progress shows how talented and creative learners are in producing puppets and telling stories , too.